Some Concerns about Richard Joyce’s Morality - Jaquet, François (International journal for the study of skepticism, 2025)
In Morality: From Error to Fiction, Richard Joyce builds a case against the existence of moral facts that consists of three independent arguments. In my assessment, these arguments are unpersuasive. The argument from naturalism presupposes that the world contains only physical facts. I present several reasons to reject such a restriction. The argument from unreliability rests on the claim that moral intuitions are untrustworthy and thus cannot justify moral beliefs. Joyce’s reasons to that effect do not hold up to critical scrutiny. The argument from responsibility states that moral facts do not exist because they necessitate moral responsibility, which is nowhere to be found. I question both premises, arguing that some moral facts do not necessitate moral responsibility and that some form of moral responsibility exists. Overall, while Joyce’s arguments are not entirely bad, I think they are not good enough to make a powerful case for error theory.